the THE EFFECTIVENESS OF HOT SEATING STRATEGY TO IMPROVE THE STUDENTS’ SPEAKING SKILL - nurul Afifah (Journal of English Education, Literature and Linguistics, 2020)
Abstract The aimed of this research was to find out the effectiveness of hot seating strategy to improve the students’ speaking skill at SMP NEGERI 3 Madang Suku III OKU TIMUR. This research adopted pre-experimental research design. The subject of this research was first students’ of SMP NEGERI 3 Madang Suku III OKU TIMUR which consisted of 31 students with 12 boys and 19 girls. Pre-test and post-test was done to collect the data. The instrument of the test was oral speaking test. Paired sample t-test was used to compare the data from pre-test and post-test. The finding showed that Mean score of pre-test was 46.63 and the mean score of post-test was 53.27. The value of t-obtained = 2.653 was more than t-table = 2.024 with df = 30 and the value of sig. (2-tailed) was 0.000 less than significance level (α = 0.05).). The conclusion, hot seating strategy was significantly effective to improve students’ speaking skill. Keywords: effectiveness, hot seating strategy, improve, speaking skill